The suitability of a simultaneous analysis and design (SAND) formulation for ground structure based sizing optimisation of geometrically non-linear structures - McDougall, Duncan John (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.